A note on two commutators - Martins-Ferreira, Nelson (2009)
We show that two known conditions which naturally arose in commutator theory and in the theory of internal crossed modules coincide: every starmultiplicative graph is multiplicative if and only if every two e ective equivalence relations commute as soon as so do their normalisations. This answers a question asked by George Janelidze.